Farum Lillevangovnene - Liebgott, Niels-Knud (Hikuin, 2001)
The Farum Lillevang kilns By Niels-Knud Liebgott Farum Lillevang is situated about 25 km north of Copenhagen. The complex of medieval kilns there was discovered in 1953 in connection with an investigation of a deserted village (mentioned in 1370) carried out by a local historical association. This was the first time that a medieval pottery workshop had been located in Scandinavia. The archaeological excavation took place in 1953 and in 1970/71 under the supervision of the National Museum of Denmark. During the first phase of the excavation the base of an oval pottery kiln – 2.6 × 4 metres in size – built partly of brick (figs. 1 & 2) was uncovered. At the south end there had been a stokepit. The kiln had without doubt had a clay dome. No further details about the construction of the kiln or kiln furniture etc. were found, apart from two “vent-stoppers” of fired clay with handles (fig. 3). The archaeological investigations in Farum Lillevang were resumed in 1970/71. At that time two rectangular brick kilns were excavated which were closely associated with the kiln previously identified. At the time of construction of the earliest of these brick kilns another oval pottery kiln had been almost completely removed, and only part of the damaged clay dome remained (fig. 5). In the remains of that kiln there were parts of the last firing, in the form of grey-fired pottery sherds which could be assembled to form five almost complete vessels. The brick kilns had been used for firing ordinary bricks, and also for architectural elements, floor tiles etc. (figs. 8-10). Unfortunately the archaeological investigations were not carried out to an acceptable academic standard. There are no available stratigraphic observations and excavation reports are virtually non-existent. Several attempts have been made – the latest initiated in 1997 by the present author – to collect C-14 and thermoluminescence datings, but without viable results. The dating of the find can however be established by a typological comparison of the pottery, and falls within the period around 1250-1350.